Effect of Hyperbaric Oxygen Therapy on Sleep Quality, Drug Dosage, and Nerve Function in Patients with Sleep Disorders after Ischemic Cerebral Stroke - Jinbiao Wang; Chunlin Wang; Xiaogang Wu; Tao Ma; Xuanming Guo (Emergency Medicine International)
Objective. To explore the effects of hyperbaric oxygen therapy (HOT) on sleep quality, drug dosage, and nerve function in patients with sleep disorders after ischemic cerebral stroke (ICS). Methods. A total of 120 patients with acute ICS and sleep disorders who came to our hospital for treatment from January 2019 to October 2021 were selected and divided into control and observation groups according to the random numbering method, with 60 cases in each group. Both groups were treated with sertraline and eszopiclone for treating insomnia. The control group was given routine treatment for ICS, and the observation group was additionally treated with HOT in addition to the control group. The sleep quality, the use of sleep medication, the neurological function score, and the levels of serum tumor necrosis factor-α (TNF-α), endothelin (ET), and neuropeptide Y (NPY) before and after treatment were compared between the two groups. Results. The levels of TNF-α, ET and NPY were not significantly different between the two groups of patients before treatment (P>0.05), and all of the above indicators decreased significantly in both groups after treatment, with the observation group being lower than the control group (P<0.05). There was no significant difference in the sleep quality scores of PSQI, ESS, and SBQ between the two groups before treatment (P>0.05), and the above indicators decreased significantly in both groups after treatment, with the observation group being lower than the control group (P<0.05). There was no significant difference in the dose of sleep medication used in the first day of treatment between the two groups (P>0.05), and the amount of sleep medication used in the observation group was significantly less than that in the control group after 14 d of treatment (P<0.05). There was no significant difference in the NIHSS scores between the two groups before treatment (P>0.05), and the scores of both groups decreased after treatment, and the scores of the observation group were significantly lower than those of the control group (P<0.05). Conclusion. Compared with routine treatment, the addition of HOT to treat patients with sleep disorders after ICS can significantly improve their sleep quality, reduce dosage of sleep drugs, reduce inflammatory level of brain tissue and nerve function damage, and improve their prognosis. Trial Registration. This study was registered in the EA2019056